2012
DOI: 10.1371/journal.pone.0045066
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of Patients with Hepatocellular Carcinoma. Validation and Ranking of Established Staging-Systems in a Large Western HCC-Cohort

Abstract: BackgroundHCC is diagnosed in approximately half a million people per year, worldwide. Staging is a more complex issue than in most other cancer entities and, mainly due to unique geographic characteristics of the disease, no universally accepted staging system exists to date. Focusing on survival rates we analyzed demographic, etiological, clinical, laboratory and tumor characteristics of HCC-patients in our institution and applied the common staging systems. Furthermore we aimed at identifying the most suita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 44 publications
4
36
1
Order By: Relevance
“…The CLIP system has been externally validated in Korean [11], Taiwanese [12], French [13], Japanese [29], American [14], German [15] cohorts. However, a study of 4525 patients in Japan had reached opposite conclusions that stratification ability and prognostic predictive power of the JIS score were much better than that of the CLIP score [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The CLIP system has been externally validated in Korean [11], Taiwanese [12], French [13], Japanese [29], American [14], German [15] cohorts. However, a study of 4525 patients in Japan had reached opposite conclusions that stratification ability and prognostic predictive power of the JIS score were much better than that of the CLIP score [9].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies comparing staging systems in HCC have revealed different ranking of staging systems [11][12][13][14][15][16][17]. However, these studies included patients with early to advanced stages, or only early to intermediate stage, or only advance stage of HCC, whereas our studied population included patients with intermediate to advanced disease that is not amenable to radical treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An advantage of using the AIC is that the best fitting model is chosen regardless of the statistical significance (or otherwise) of any change in infection rates. The AIC is a useful statistic for quantifying the evidence for a set of competing models, 19 and it has been used in a wide variety of model selection problems, including choosing between competing sets of independent variables, 20 prediction models, 21 and covariance structures. 22 For the best model in each state, we estimated the per- figure 3.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, the BCLC classification has been validated in different clinical settings [8,9,10,11]. However, recent studies from Taiwan and Germany have demonstrated that the CLIP system is the best prognostic model in patients with HCC [12,13,14]. Therefore, it remains unclear which of these staging systems can most accurately predict the prognosis of patients with HCC.…”
Section: Introductionmentioning
confidence: 99%